Meningkatkan Literasi Bahasa Indonesia di Era Digital - ValenTina Pinem; Violetta Olga Putri Nadely; Esmeralda Sitohang; Joharis Lubis (Pusat riset dan Inovasi Nasional, 2024)
The study focuses on the significance of Indonesian language literacy in the context of the digital era, highlighting the complexities and challenges in learning and practicing literacy due to technological advancements. The primary objective is to identify effective methods for enhancing literacy skills amidst the proliferation of misinformation and hoaxes, emphasizing that literacy extends beyond reading and writing to include critical thinking skills necessary for evaluating valid information. This article employs a qualitative approach through literature review, presenting various strategies such as integrating technology into learning, promoting a reading culture, developing digital content in Indonesian, and systematically instilling digital literacy. The key findings underscore the essential role of multiple stakeholders in fostering a literacy culture that adapts to contemporary challenges. Ultimately, this research aims to serve as a reference for developing more effective literacy policies and programs that enhance Indonesian language literacy skills in the face of rapid technological advancements.